(untitled) (Global Journals of Research in Engineering, 2011)
With a view to provide cooling, heating, ventilation, humidity/contaminant control and pressurization within aircraft occupied compartments, cargo compartments and electronic equipment bays Environmental Control system is a part of all Military and civil aircrafts . It also caters to other pneumatic demands like windshield demisting, aerofoil anti-icing, door-sealing, fuel-tank pressurization and engine bay ventilation. The technology used for air conditioning of all types of Military/Civil aircrafts is predominantly Air Cycle air Conditioning. Based upon Joule or Reversed Brayton Cycle, the system utilizes the high temperature, high pressure bleed air extracted from compressor of main engine/APU. It not only enjoys the advantage of simplicity and inherent compactness of pneumatic equipment but also meets the integrated cooling and pressurization requirements of an aircraft. Both air-cycle based refrigeration system which lowers the enthalpy level of air by transforming heat energy into work and conventional vapor compression cooling system that extracts heat by evaporating a suitable liquid refrigerant have their own limitations.